PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP HASIL BELAJAR FISIKA PESERTA DIDIK KELAS XI MIPA - Karmilawati, Afni; Rahmi, Aidhia (Jurnal Riset Fisika Edukasi dan Sains, 2019)
The background of this research  not all students like physics learning. This is caused by students' lack of understanding of physics learning material. The students' incomprehension can be seen when the learning process takes place, some students are embarrassed to ask even though basically the students do not understand the material presented by the teacher in front of the class. This type of research is Quasi Experiment with research design in the form of Design Group Control. Data on physics learning results are seen in two domains, namely the cognitive and affective domains. In the cognitive domain, the average experimental class has an average of 67.37 while the class has an average of 60.76. Learning outcomes in the affective domain obtained from the assessment of student activity sheets had an average of 79 in the experimental class and 74 in the control class. Based on the results of the analysis of hypothesis testing with the F test, it was found that t count = 1.64, and t table = 2.00, where if –t table < t count < t table then the hypothesis is rejected. So it can be concluded that the use of cooperative learning model type Group Investigation does not affect the learning outcomes of physics students of class XI MIPA SMAN 1 Enam Lingkung.